2020
DOI: 10.35508/ljch.v2i1.2824
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between 3M+ Behavior and The Incidence of Dengue Hemorrhagic Fever in Kupang City

Abstract: Indonesia is a dengue-endemic area. DHF in Kupang City in 2014 was 487 cases, in 2015 was 665 cases, in 2016 was 1.213 cases, it was 2019 387 cases. The 3M+ behavior includes the habit of draining water storage, closing the water storage, burying old stuff, sowing larvicide powder, using mosquito insecticide, using mosquito bed-net, and avoiding the habit of hanging clothes. This study aims to analyze the relationship between 3M+ behavior and the incidence of DHF. This study was conducted in September 2019. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…The 3M Plus action is carried out to eradicate and destroy the dengue mosquito vector chain. A previous study by Moreira showed that 3M Plus activities such as draining and covering water reservoirs, as well as using mosquito repellent insecticides were related to the dengue incidence [17] This has a significant impact in controlling breeding places for mosquito nests and eradicating larvae before growing into adult mosquitoes. Moreover, prevention and control of dengue are carried out earlier [18].…”
Section: Discussionmentioning
confidence: 99%
“…The 3M Plus action is carried out to eradicate and destroy the dengue mosquito vector chain. A previous study by Moreira showed that 3M Plus activities such as draining and covering water reservoirs, as well as using mosquito repellent insecticides were related to the dengue incidence [17] This has a significant impact in controlling breeding places for mosquito nests and eradicating larvae before growing into adult mosquitoes. Moreover, prevention and control of dengue are carried out earlier [18].…”
Section: Discussionmentioning
confidence: 99%
“…Larvasida adalah bahan yang digunakan untuk membunuh hama serangga pada tingkat larva yang hidup di dalam air dan belum mencapai ukuran dewasa (Moreira et al, 2020). Penggunaan larvasida ini dapat menekan kepadatan populasi untuk jangka waktu 2 bulan.…”
Section: Pendahuluanunclassified
“…Sumber utama perkembangbiakan nyamuk aedes aegypti adalah wadah penyimpanan air untuk kebutuhan rumah tangga sehari-hari. Wadah penyimpanan air harus harus selalu tertutup rapat dengan petutup yang pas dan harus ditempatkan kembali dengan benar setelah mengambil air (20).…”
Section: Agung Sutriyawanunclassified